2009
DOI: 10.1007/s10695-009-9308-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of fish spermatozoa during semen storage

Abstract: This mini-review focuses on changes in ATP and creatine phosphate concentrations in fish sperm under storage conditions. The storage of catfish sperm at 4 degrees C leads to ATP depletion and decreased sperm motility. The rate of intracellular ATP depletion can be diminished through the addition of energetic substrates to the sperm storage medium, with lactate + pyruvate being the most efficient substrates for maintaining ATP concentrations in catfish sperm. The decrease in ATP concentration is closely associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Limited information is available on substrates and metabolite levels of energy resources (Terner & Korsh 1963; Billard & Cosson 1990; Lahnsteiner, Patzner & Weismann 1992, 1993; Lahnsteiner et al . 1999) and the enzymes involved in energetic nucleotide metabolism in fish sperm (Lahnsteiner et al . 1996, 1998; Weismann, Weismann & Patzner 1997; Rurangwa, Biegniewska, Slominska, Skorkowski & Ollevier 2002; Mansour, Lahnsteiner & Berger 2003; Gronczewska, Ziȩtara, Biegniewska & Skorkowski 2003; Grzyb, Rychłowski, Biegniewska & Skorkowski 2003; Grzyb & Skorkowski 2006; Ziętara, Biegniewska, Rurangwa, Swierczynski, Ollevier & Skorkowski 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Limited information is available on substrates and metabolite levels of energy resources (Terner & Korsh 1963; Billard & Cosson 1990; Lahnsteiner, Patzner & Weismann 1992, 1993; Lahnsteiner et al . 1999) and the enzymes involved in energetic nucleotide metabolism in fish sperm (Lahnsteiner et al . 1996, 1998; Weismann, Weismann & Patzner 1997; Rurangwa, Biegniewska, Slominska, Skorkowski & Ollevier 2002; Mansour, Lahnsteiner & Berger 2003; Gronczewska, Ziȩtara, Biegniewska & Skorkowski 2003; Grzyb, Rychłowski, Biegniewska & Skorkowski 2003; Grzyb & Skorkowski 2006; Ziętara, Biegniewska, Rurangwa, Swierczynski, Ollevier & Skorkowski 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After initiation of sperm motility in the aquatic environment, duration of motility is very short in fishes from a few seconds to several minutes or hours depending on the species [28,29,51,59,65,66]. The inter-species differences probably depend on the capacity of the sperm to restore intracellular ATP and creatine phosphate concentrations [67,68]. Once sperm motility is initiated, the percentage of motile sperm and sperm velocity rapidly decrease, which are associated with a large, but not complete depletion of ATP [46,59,66] (Figure 3B).…”
Section: Sperm Motilitymentioning
confidence: 99%
“…Nonetheless, Burness et al (2005) concluded that the significance of a negative relationship between swimming speed and LDH activity was unclear. On the other hand, assuming that LDH activity reflects glycolytic activity, one can suggest that a high LDH activity is indicative of a high capacity to produce ATP (Zietara et al 2009). However, the calculations on the basis of in vitro enzyme activity determinations are probably overestimates because they are made in the presence of saturated concentrations of substrates.…”
Section: Characteristicmentioning
confidence: 99%
“…However, the calculations on the basis of in vitro enzyme activity determinations are probably overestimates because they are made in the presence of saturated concentrations of substrates. Since the availability of endogenous substrates has not been taken into consideration, these calculations should be interpreted with caution (Zietara et al 2009). There is considerable variation among species in the identity of fuels (i.e., glycolytic or lipidic as explored in this study) used to support sperm motility (Mansour et al 2003).…”
Section: Characteristicmentioning
confidence: 99%